The Manx verbal noun revisited - Broderick, George (Journal of Celtic linguistics, 2017)
This note looks at the thesis proposed by Christopher Lewin that the verbal noun in Manx over time became 'verbalised' or a 'true verb'. My note looks at three aspects of Lewin's thesis: (a) the verbal noun itself, (b) nominal prepositions and (c) the attachment of * - ag - - to verbal-nouns with vocalic anlaut; and I suggest that all three are connected in the context of the onset of syncretism in Manx Gaelic and thereby reach a different conclusion.